Blast furnace and metallurgical coke's reactivity and its determination by thermal gravimetric analysis. (September 2015) - Rodero, J. I.; Sancho-Gorostiaga, J.; Ordiales, M.; Fernández-González, D.; Mochón, J.; Ruiz-Bustinza, I.; Fuentes, A.; Verdeja, L. F.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of the present work is to adapt tests that are typically used for blast furnace cokes, such as coke reactivity index (CRI) and coke strength after reaction, to ferroalloy production in electric furnaces by developing easier equipment that meets with ISO 18894 standards. Moreover, a new technique has also been developed using thermal gravimetric analysis in order to quickly, inexpensively and reliably find the CRI parameter. As result of this work, a polynomial relationship between coke's reactivity and mass loss slopes of the record line obtained in the gravimetric thermal analysis tests was found.